2D Materials: The Influence of Water on the Optical Properties of Single‐Layer Molybdenum Disulfide (Adv. Mater. 17/2015). (May 2015) - Varghese, Joseph O.; Agbo, Peter; Sutherland, Alexander M.; Brar, Victor W.; Rossman, George R.; Gray, Harry B.; Heath, James R.
<x xml:space="preserve">Abstract</x> A scanning probe image of single‐layer MoS2 trapping water on a mica surface is depicted on the left, with its corresponding photoluminescence image depicted on the right. The trapped water strongly quenches the fluorescence of single‐layer MoS2 and distinctly affects its optical properties. The work by J. R. Heath and co‐workers on page 2734 highlights the significance of the local chemical environment in determining the opto‐electronic properties of 2D materials.